PELATIHAN SOFTWARE AKUNTANSI ACCURATE DI SMU TARSISIUS I - Chelsya; Fernanda, Vira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT Technological developments demand that all systems must be computerized including accounting. The existence of Accurate Accounting Software facilitates the process of recording transactions and the process of financial reporting. However, until before the training was held, Tarsisius I High School students had never received knowledge about Accurate Accounting Software so that it became a problem that had to be resolved. The solution to the problems is to hold Accurate Accounting Software training for Tarsisius I High School students via Zoom Meeting. The method used in the implementation of PKM is a training method accompanied by pre-test and post-test in the form of quizzes. The implementation of the Accurate Software training at Tarsisius I High School has achieved satisfactory results when seen from the comparison of the quiz scores before and after the training. The author's expectation is that Tarsisius High School students are interested in continuing to study Accounting and accounting software. ABSTRAK Perkembangan teknologi menuntut semua sistem harus terkomputerisasi termasuk Akuntansi. Adanya Software Akuntansi Accurate mempermudah proses pencatatan transaksi dan proses pelaporan keuangan. Namun sampai sebelum pelatihan diadakan, siswa SMU Tarsisius I belum pernah mendapat pengetahuan mengenai Software Akuntansi Accurate sehingga menjadi permasalahan yang harus diselesaikan. Solusi atas permasalahan mitra adalah dengan mengadakan pelatihan Software Akuntansi Accurate kepada siswa SMU Tarsisius I melalui Zoom Meeting. Metode yang digunakan dalam pelaksanaan PKM adalah metode pelatihan disertai pre test dan post test berupa kuis. Pelaksanaan pelatihan Software Accurate di SMU Tarsisius I telah mencapai hasil yang memuaskan apabila dilihat dari perbandingan nilai kuis sebelum dengan setelah pelatihan. Ekspektasi penulis adalah siswa SMU Tarsisius berminat untuk terus mempelajari ilmu Akuntansi beserta software Akuntansi.